2012
DOI: 10.1007/s11524-012-9684-8
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Youth in Food Activism in New York City: Lessons Learned from a Youth Organization, Health Department, and University Partnership

Abstract: Research indicates that insufficient emphasis on community collaboration and partnership can thwart innovative community-driven work on the social determinants of health by local health departments. Appreciating the importance of enhancing community participation, the New York City Department of Health and Mental Hygiene (DOHMH) helped lead the development of the Health Equity Project (HEP), an intervention aimed at increasing the capacity of urban youth to identify and take action to reduce food-related healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Participants also described how the project helped them develop leadership and public-speaking skills that resulted in increased self-efficacy and confidence in advocating for changes within their families and community. These outcomes are similar to what have been identified by other youth-engaged participatory research efforts, 57,63,73 thus reinforcing the unique opportunities a youth-focused approach to research has for building capacity and mobilizing community members on health issues.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Participants also described how the project helped them develop leadership and public-speaking skills that resulted in increased self-efficacy and confidence in advocating for changes within their families and community. These outcomes are similar to what have been identified by other youth-engaged participatory research efforts, 57,63,73 thus reinforcing the unique opportunities a youth-focused approach to research has for building capacity and mobilizing community members on health issues.…”
Section: Discussionsupporting
confidence: 74%
“…As reflected in prior studies, the students recognized that dietary habits are shaped by social and environmental factors, including household norms and behaviors, transportation, availability of healthful food, convenience, and cost. 28,[63][64][65][66] A common theme in the focus groups was the lack of access to healthful food coupled with an abundance of affordable, unhealthy food. 57 Students also recognized that neighborhoods are segregated by race/ethnicity and socioeconomic factors, and this segregation creates disparities in access to higher-quality, more healthful foods.…”
Section: Discussionmentioning
confidence: 99%
“…Strategic alignment and evaluation results inform each other in a gradual transformation process (Ali, 2009). The results are also synergized with the findings of Tsui et al, 2012, which concluded that community collaboration and partnership is one innovative work community based on determinants of social health.…”
Section: Discussionsupporting
confidence: 55%
“…Youth may prove to be important change agents for their communities, as researchers have found training youth to be community leaders is an effective strategy for improving public health (Curran, Ned, & Winkleby, 2014; Jones, Spence, Hardin, Clemente, & Schoch, 2011; Tsui, Bylander, Cho, Maybank, & Freudenberg, 2012; Wyman et al, 2010). Public health advocacy is central to health promotion, and programs focusing on skills development of youth in this area are central to effective practice.…”
Section: Introductionmentioning
confidence: 99%